PERENCANAAN TATA RUANG BERBASIS PARTISIPASI MASYARAKAT DALAM MITIGASI BENCANA ALAM DI KELURAHAN LAKSANA KOTA BANDA ACEH - Ahmad Rozi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
The research aims at studying participatory spatial planning in mitigating natural disaster in Banda Aceh City. It employs inductive-qualitative, phenomenological method in which the researcher tries to recognize and identify the meanings of realities, then illustrate them into a conceptual construction. The result of the research at Kelurahan Laksana Banda Aceh City shows that participatoryspatial planning in mitigating natural disaster does not work well due to several obstacles such as lack of coordination. Good coordination only occurs among government officers at sub-district level but not at the village (kelurahan) level. Donor bodies in the rehabilitation and reconstruction process tend be merely project accomplishment-oriented. They are concerned about physical aspectsbut not social, psychological and cultural aspects. Spatial planning following tsunami disaster does not cover cultural, social, and religious aspects and norms of local people. At the same time, local people participation in the spatial planning is not optimal yet. Although local people contribute ideas, development agents (donors and government) do not take them into account. As a result, the spatial planning does not answer local needs.